Implementation of preemptive fluid strategy as a bundle to prevent fluid overload in children with acute respiratory distress syndrome and sepsis - Franco Díaz; María José Nuñez; Pablo Pino; Benjamín Erranz; Pablo Cruces (BMC, 2018)
Abstract Background Fluid overload (FO) is associated with unfavorable outcomes in critically ill children. Clinicians are encouraged to avoid FO; however, strategies to avoid FO are not well-described in pediatrics. Our aim was to implement a bundle strategy to prevent FO in children with sepsis and pARDS and to compare the outcomes with a historical cohort. Methods A quality improvement initiative, known as preemptive fluid strategy (PFS) was implemented to prevent early FO, in a 12-bed general PICU. Infants on mechanical ventilation (MV) fulfilling pARDS and sepsis criteria were prospectively recruited. For comparison, data from a historical cohort from 2015, with the same inclusion and exclusion criteria, was retrospectively reviewed. The PFS bundle consisted of 1. maintenance of intravenous fluids (MIVF) at 50% of requirements; 2. drug volume reduction; 3. dynamic monitoring of preload markers to determine the need for fluid bolus administration; 4. early use of diuretics; and 5. early initiation of enteral feeds. The historical cohort treatment, the standard fluid strategy (SFS), were based on physician preferences. Peak fluid overload (PFO) was the primary outcome. PFO was defined as the highest FO during the first 72 h. FO was calculated as (cumulative fluid input - cumulative output)/kg*100. Fluid input/output were registered every 12 h for 72 h. Results Thirty-seven patients were included in the PFS group (54% male, 6 mo (IQR 2,11)) and 39 with SFS (64%male, 3 mo (IQR1,7)). PFO was lower in PFS (6.31% [IQR4.4-10]) compared to SFS (12% [IQR8.4-15.8]). FO was lower in PFS compared to CFS as early as 12 h after admission [2.4(1.4,3.7) v/s 4.3(1.5,5.5), p < 0.01] and maintained during the study. These differences were due to less fluid input (MIVF and fluid boluses). There were no differences in the renal function test. PRBC requirements were lower during the first 24 h in the PFS (5%) compared to SFS (28%, p < 0.05). MV duration was 81 h (58,98) in PFS and 118 h (85154) in SFS(p < 0.05). PICU LOS in PFS was 5 (4, 7) and in SFS was 8 (6, 10) days. Conclusion Implementation of a bundle to prevent FO in children on MV with pARDS and sepsis resulted in less PFO. We observed a decrease in MV duration and PICU LOS. Future studies are needed to address if PFS might have a positive impact on health outcomes.